PENGEMBANGAN E-MODUL BERBASIS MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) PADA MATERI SPLDV TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Lathifah, Miskatul; Putra, Yudi Yunika; Lathiifah, Iis Juniati (Universitas Muhammadiyah Semarang, 2024)
This research aims to produce the characteristics of e-modules based on the creative problem solving (CPS) learning model on SPLDV material on valid, practical problem solving abilities, as well as to determine the potential effects of using e-modules based on the creative problem solving (CPS) learning model on the material. SPLDV on problem solving abilities. This type of research is the Research and Development (R&D) method using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of this research involved students in class VIII of one of the state junior high schools in Airgegas for one to one trials, totaling 3 students in class VIII4, small group trials, totaling 9 students in class VIII4, field trials, totaling 21 participants. class VIII4 students, and a pilot test consisting of 30 class VIII2 students. Data collection techniques were carried out by means of interviews, questionnaires and tests (pretest and posttest). The data analysis techniques used are qualitative descriptive and quantitative descriptive. This research produces characteristics of an e-module based on a creative problem solving (CPS) learning model that is valid and practical, and has a potential effect on students' problem solving abilities.